Media Disc Triage Assessment on Improving Triage Skills Using the Australasian Triage Scale (ATS) on Students of Kusuma Husada University Surakarta - Rosida, Nikma Alfi; Afni, Annisa Cindy Nurul; Rahmad, Muhamad Nur (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2024)
ABSTRACT The Australasian Triage Scale (ATS) is a tool used by triage officers in the emergency department to assess patient severity and prioritize services based on the severity of the patient's condition. To evaluate the effectiveness of using learning tools in the form of Disc Triage Assessment as a learning medium in improving understanding and accuracy in determining triage by nursing students in using ATS triage. The Community Service method used is quasi-experimental with a pre-post test without control design. Community Service will be carried out on Nursing Study Program Students, Diploma Three Program, Faculty of Health Sciences, Kusuma Husada University. Data analysis was performed using the Wilcoxon test. The pretest results showed that the moderate category was 1 respondent (3.1%) and the poor category was 31 respondents (96.9%). The posttest results with the Good category were 3 respondents (9.4%) and the Fair category were 5 respondents (75.0%). The results of the use of Disc Triage Assessment media show that the p-value is 0.016 (<0.05) which means that there is an effect of Disc Triage Assessment Media on Skills to Determine Australasian Triage Scale (ATS) on Students of Kusuma Husada University Surakarta. Keywords: Media Disc Triage Assessment, Triage skills, Australasian Triage Scale (ATS)